PHOTOCATALYTIC DEGRADATION OF METRONIDAZOLE BY \(TiO_2\) AND \(Bi_2\)\(Se_2\)\(Te\)-\(TiO_2\) NANOMATERIALS - Huu Phuoc Le; Nguyen Hong Khanh Cao; Chi Toan Nguyen; Long Quan Dang; Thi Hong Nguyen; Thi Cam Tuyen Le; Chau Minh Vinh Tho Do (Tạp chí Khoa học Đại học Đà Lạt)
Antibiotic residues in aquaculture wastewater pose a significant environmental challenge, as conventional wastewater treatment plants are often ineffective in their removal. To overcome this challenge, this study developed TiO2 nanowires on nanotube arrays (TNWs/TNAs) and further enhanced them with Bi2Se2Te nanoparticle (NP) decoration for efficient photocatalytic degradation of metronidazole. The TNWs/TNAs were fabricated through anodization in an aqueous solution of NH4F/ethylene glycol, while Bi2Se2Te NPs were obtained via a plasma-assisted exfoliation technique and subsequently deposited onto the TNWs/TNAs. The photocatalytic efficiency of TNWs/TNAs and Bi2Se2Te-TNWs/TNAs was evaluated by monitoring the degradation of metronidazole under ultraviolet-visible (UV-Vis) illumination using the HPLC-PDA method. All TiO2 nanostructures exhibited the anatase phase and displayed a distinct morphology, characterized by nanowires extending from nanotube arrays. The decoration of Bi2Se2Te nanoparticles onto TNWs/TNAs was visualized through SEM imaging and further validated using EDS, UV-Vis absorption spectroscopy, and Raman spectroscopy analysis. Both TNWs/TNAs and Bi2Se2Te-TNWs/TNAs effectively and rapidly degraded metronidazole, achieving removal efficiencies of 71.8% and 83.0% after 20 minutes of UV-Vis irradiation (100 mW·cm⁻²), respectively. Furthermore, the reaction rate constant of Bi2Se2Te-TNWs/TNAs (85.4 × 10-3 min-1) was higher than that of TNWs/TNAs (60.7×10-3 min-1), which was primarily attributed to the localized surface plasmon resonance (LSPR) effect of Bi2Se2Te NPs and enhanced charge separation within the hybrid Bi2Se2Te-TNWs/TNAs system. These findings demonstrate that Bi2Se2Te-TNWs/TNAs exhibit superior photocatalytic performance for antibiotic degradation, offering a promising strategy for wastewater treatment.